On the issue of borrowing Russian vocabulary in the business sphere of the Kazakh language - Abildayeva К.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article compares the materials of dictionaries and reference books of the official business vocabulary of the Kazakh language in the 80-90s. XX century. and the beginning of the XXI century, which testifies to a steady trend towards a reduction in the number of Russianisms and active word-formation processes with the involvement of both our own linguistic resources and word-formation models of the Russian language. Comparative analysis of dictionaries and reference books, depending on the year of issue, shows changes in the composition and structure of terms due to new conditions for the development of the Kazakh language. At the present time, the Russian language acts as an intermediary language in the process of involving European borrowings in the vocabulary of the Kazakh language. The influence of the Russian language is also found in the vocabulary of the Kazakh language of samples for tracing certain models of word formation. In the Kazakh language, there is a tendency towards widespread use of internal nominative resources